1990
DOI: 10.1149/1.2086218
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Regeneration of the Neodymium Oxide Reduction‐Spent Salt

Abstract: A theoretical analysis of the relevant thermodynamic and electrochemical data revealed that the electrolytic regeneration of the calcium reductant and the solvent salt from the spent salt of the neodymium oxide reduction process is feasible. Electrolytic decomposition of normalCaO dissolved in CaCl2‐CaF2 molten salt between a graphite anode and a Ca‐Zn molten pool cathode was achieved at a potential higher than 2.2V, which was determined from current‐voltage curves. Calcium recovery in the range of 10 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In line with the reported observations, [24,27,32] in the present case, it was observed that both the electrolyte and foam were contaminated with carbon dust, which emerged as an undesired product (of parasitic/unwanted reactions) during the deoxidation reaction. The source of the carbon contamination could be ascribed to the occurrence of one or more reactions as follows.…”
Section: F Carbon Contamination During Deoxygenationsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with the reported observations, [24,27,32] in the present case, it was observed that both the electrolyte and foam were contaminated with carbon dust, which emerged as an undesired product (of parasitic/unwanted reactions) during the deoxidation reaction. The source of the carbon contamination could be ascribed to the occurrence of one or more reactions as follows.…”
Section: F Carbon Contamination During Deoxygenationsupporting
confidence: 93%
“…(a) According to Kipouros et al, [32] the presence of CaCO 3 in CaCl 2 can result in the formation of carbon. This compound can either be present in CaCl 2 as an impurity or is generated during the reduction/deoxygenation by the following set of side reactions:…”
Section: F Carbon Contamination During Deoxygenationmentioning
confidence: 99%
“…This oxygen-gas evolution, however, requires an oxidation-resistive material such as a nonconsumable anode material. [22,24,28,[39][40][41][42][43][44] However, it was not easy to deposit either pure liquid Ca or a liquid Ca alloy with a good yield and a good current efficiency, because the precipitated Ca dissolved immediately back into the salt and parasitic reactions occurred. Instead of using a nonconsumable anode for O 2 gas evolution, a consumable carbon anode can lower the potential by 1.03 V. [4][5][6]8,[39][40][41] At the anode: C + 2 O 2− = CO 2 (gas) + 4e − , C + O 2− = CO (gas) + 2e − [5] At the cathode: Ca 2+ + 2e − = Ca [6] Even in case of a low activity of CaO (a CaO ), the decomposition voltage of CaO remains much lower than that of CaCl 2 decomposition, as shown in Figure 2.…”
Section: Electrolysis Of Cao In Molten Caclmentioning
confidence: 99%
“…The conceptual image of the two reaction vessels (Figure 4) was proposed in calciothermic reduction of TiO 2 , Nd 2 O 3 , and radioactive elements. [2,3,[39][40][41][42] Ca or Ca formed at the cathode is passed with a part of the molten salt toward the reduction vessel and is used for the reduction of the oxide powder. The byproduct, CaO, and the solvent CaCl 2 are returned to the upper vessel.…”
Section: Combination Of Reduction and Electrolysismentioning
confidence: 99%
“…Regarding the electrochemical behavior of the liquid Zn electrode, Kipouros and Sharma reported electrolysis of a Ca-Zn liquid alloy in the molten CaCl 2 -CaO-CaF 2 system at 973-1023 K. 61 However, the electrode potential was unclear because a two-electrode system was employed. In the present study, we investigated the effective potential range for the production of Si-Zn alloy by electrolysis of SiO 2 granules on the Zn electrode.…”
Section: H5050mentioning
confidence: 99%